Into the Unknown: Onboarding Early Career Professionals in a Remote Work Environment - Martyniuk, Julia; Moffatt, Christine; Oswald, Kevin (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2021)
This paper explores the impact of the COVID-19 pandemic from the perspective of three individuals, all of whom are early-career professionals: Julia, a term librarian for an academic library who began her role as the pandemic was causing widespread change; Christine, a recent graduate who started her job search during the pandemic; and Kevin, a current Master of Library and Information Science student who started and completed his co-op in an entirely remote setting. This paper explores their perspectives on job precarity in a remote work environment and provides reflections on working in a library setting during the pandemic. To bring together the key themes experienced throughout this period, several recommendations are offered to managers and early-career librarians as they navigate this new landscape. For employers, advertising new employees, organizing their onboarding, and ensuring concerted efforts for introductions are recommended. For new librarians, forming communities of practice and building relationships in the remote work environment to battle feelings of isolation and not belonging are recommended. The precarious roles most early-career librarians find themselves in is unlikely to improve during the pandemic. The perspectives and reflections shared in this paper are intended to provide a transparent view into the experiences of three early career librarians, what they have learned, and how they are maximizing their time in the remote work environment.